2014
DOI: 10.1007/s10798-014-9298-4
|View full text |Cite
|
Sign up to set email alerts
|

Fostering creativity from an emotional perspective: Do teachers recognise and handle students’ emotions?

Abstract: Emotions have a significant effect on the processes of designing and creative thinking. In an educational context, some emotions may even be detrimental to creativity. To further explore the link between creativity and emotion, a series of interviews were conducted with design and technology (D&T) teachers in Singapore, Hong Kong and Beijing concerning their experiences of working with students on design projects. The intent was to investigate how these teachers understood and managed their students' emotions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
(70 reference statements)
0
7
0
1
Order By: Relevance
“…Similarly, the study substantially validated the findings regarding the teachers' EI and their creative performance, hence endorsing the study from Siu and Wong (2016), however, the results failed to validate the relationship between teachers' creative performance and their learning outcomes in HEIs. Hence, this study is a contradictory piece of research in relation to Li et al (2017).…”
Section: Discussion Conclusion and Practical Implications Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Similarly, the study substantially validated the findings regarding the teachers' EI and their creative performance, hence endorsing the study from Siu and Wong (2016), however, the results failed to validate the relationship between teachers' creative performance and their learning outcomes in HEIs. Hence, this study is a contradictory piece of research in relation to Li et al (2017).…”
Section: Discussion Conclusion and Practical Implications Discussionmentioning
confidence: 51%
“…Creative self-efficacy and leadership/supervisor support are two vital components of creative performance ( Shalley and Gilson, 2004 ; Walumbwa et al, 2018 ) that are taken as indicators of creative performance in this study. A recent study investigated the association between personnel EI and their creativity, establishing that EI is vital for creative performance ( Darvishmotevali et al, 2018 ) exclusively in the education sector ( Siu and Wong, 2016 ). The education sector, however, lacks a realistic literary indication regarding EI and creative performance ( Rodrigues et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although creativity is a fundamental element of engineering, a recent literature review reveals that very little is known about how to teach for creativity . In cases when unleashing student creativity is an expected outcome, teachers must find ways to stimulate students’ imagination, break their fixation, spur their exploration, and even manage their emotions . However, studies found that, while many teachers value the concept of creativity, there exists a discrepancy between their claims of valuing creativity and the realities of their classrooms .…”
Section: Challenges In Secondary Engineering Educationmentioning
confidence: 99%
“…Affective education is used as an educational concept and a part of the educational process, which is concerned with the findings, beliefs, attitudes, and emotions of students with their interpersonal relationships and social skills [29]. Since 1970s, the research of affective education has changed from the initial stage to the development stage, and related works research mainly focused on emotional education theory and affective education model, such as humanistic emotion theory [36], academic achievement emotion theory [41], scaffolding affective education theory [24] and affective education practice model [9] [33]. Among them, humanistic emotion theory emphasizes self-expression, emotion and subjectivity, and it not only pays attention to the development of cognition in teaching process, but also pays more attention to learners emotion, motivation and interest.…”
Section: Affective Educationmentioning
confidence: 99%